Accommodation of Islamic Culture in Indonesia: Harmony Between Islamic Teachings and Local Traditions - Lina Khoerunnisa; Salma Sahda; Tiyas Endah (Penerbit Hellow Pustaka, 2025)
The accommodation of Islamic culture in Indonesia is a process of adjustment and harmonization between Islamic teachings and local traditions that already exist in society. Islam in Indonesia is not present in a rigid manner, but is able to adapt to local culture as long as it does not conflict with Islamic law. For example, the Batak martolog tradition honors the dead, and there are also earth alms and sea alms traditions that combine elements of religion and elements of environmental preservation. This process allows Islam to be widely accepted and coexist harmoniously with local culture, enriching religious practices while maintaining the community's cultural identity. This accommodation is also reflected in the distinctive traditions, arts, languages and social patterns of various regions in Indonesia. Thus, Islamic cultural accommodation not only strengthens the faith of the ummah, but also builds tolerance and social cohesion in a plural and multicultural society.